Glycodeoxycholic acid as alternative treatment in 3β-hydroxy-Δ5-C27-steroid-oxidoreductase: a case report - S. Majait; F. M. Vaz; F. M. Vaz; F. M. Vaz; E. Marleen Kemper; A. H. Bootsma; A. K. Groen; M. Nieuwdorp; Maarten R. Soeters (Frontiers Media S.A., 2024)
Background3β-hydroxy-Δ5-C27-steroid-oxidoreductase (3β-HSD) deficiency is a bile acid synthesis disorder that leads to the absence of normal primary bile acids and the accumulation of abnormal bile acids. This results in cholestatic jaundice, fat-soluble vitamin deficiency, acholic or fatty stools and failure to thrive. Bile acid supplementation is used to treat 3β-HSD-deficiency and its symptoms.MethodsThis report details the case of a 28-year-old woman diagnosed with 3β-HSD-deficiency, who was treated with glycine-conjugated deoxycholic acid (gDCA).ResultsgDCA treatment successfully restored normal bile acid levels, improved body weight by reducing fat malabsorption, and was well-tolerated with no observed liver problems or side effects.ConclusionsAs a potent FXR ligand, gDCA might exert its action through FXR activation leading to bile acid synthesis regulation.